Institutional Reform for Innovation and Entrepreneurship: An Agenda for Europe - Magnus Henrekson (SpringerBriefs in Economics, 2017)
The authors of this book advise the economies of the European Union to become more entrepreneurial in promoting innovation and economic growth. The authors propose a reform strategy with respect to several aspects to achieve this goal. Starting with the rule of law and the protection of property rights; the tax system; the authors deal with regulations governing savings, capital and finance, and the organization of labor markets and social insurance systems. Framework strategies related to the regulations governing goods and service markets, bankruptcy and insolvency are also put forward. A core understanding and future path is also provided towards R&D, commercialization and knowledge spillovers; human capital investments; and informal institutions.